Serum Beta‐Synuclein Is Higher in Down Syndrome and Precedes Rise of pTau181. Issue 1 (12th April 2022) - Oeckl, Patrick; Wagemann, Olivia; Halbgebauer, Steffen; Anderl‐Straub, Sarah; Nuebling, Georg; Prix, Catharina; Loosli, Sandra V.; Wlasich, Elisabeth; Danek, Adrian; Steinacker, Petra; Ludolph, Albert C.; Levin, Johannes; et al.
Abstract : This exploratory case–control study investigates the synaptic marker beta‐synuclein in serum and plasma pTau181 in adults with Down syndrome (DS) with (sDS, n = 14) and without (aDS, n = 47) clinical symptoms of Alzheimer disease (AD) as well as euploid controls ( n = 23). Beta‐synuclein was higher in aDS and more pronounced in sDS ( p < 0.0001), whereas pTau181 was only higher in sDS ( p < 0.0001). Both markers showed good discriminatory power (area under the curve > 0.90) to distinguish symptomatic from asymptomatic AD. The data indicate that synaptic alterations belong to the earliest AD‐associated events in DS and highlight the value of serum beta‐synuclein as a potential early marker of AD. ANN NEUROL 2022;92:6–10